Transport Connectivity and Health Care Access Evidence from Liberia - Iimi, Atsushi (The World Bank, 2018)
Health care access is an important policy concern, especially in rural areas. It is especially challenging in developing countries, where rural residents are poorer and less likely to be insured than those living in urban areas. Using the case of Liberia, this paper examines the effects of transport connectivity on health care access. The Ebola crisis in 2014 and 2015 clearly revealed the vulnerability of the country's transport and health systems to unexpected external shocks. Paying particular attention to the possible challenge of endogeneity associated with infrastructure investment, the study found that transport connectivity, especially greater road density, can increase access to health care, but there was no significant effect of road quality. This may be because of significantly skewed underlying data. The vast majority of roads in Liberia are in poor condition. The study also found that the statistical effect of road density varies depending on distance from a health facility. The effect is particularly significant within a 30- to 50-kilometer radius. Not only rural accessibility, but also broader transport connectivity needs to be developed to increase health care access